(untitled) (Asia Pacific Journal of Social Innovation, 2024)
Newborn bathing for babies is considered to be an effective preventive measure to reduce infection caused by microorganisms. However, the sterility of these commonly used basins has been disregarded in some hospitals in Iligan City which could risk the newborn’s health. any alteration and microbial invasion to the newborn’s weak immune system. Bacteriological assessment was done for the bath basins of the Neonatal Intensive Care Unit (NICU) at Gregorio T. Lluch Memorial Hospital, ligan City. Samples were obtained via swabbing at the lateral sides and center part of the basins that were used before and after newborn bathing. Swab samples were then placed in screw-capped tubes with 10 ml of nutrient broth and were immediately transported at the microbiological laboratory for characterization and identification of the bacterial isolates using the conventional methods. Among the identified bacteria isolated, Neisseria spp. was in great number constituting more than half of the samples (26 out of 44 isolates, 59.1%. These are gram-negative cocci that are obligate human pathogens with no other natural hosts. Results can be associated through possible bacterial transmission during newborn delivery and newborn bathing whereby such bacteria are capable of residing on areas of the bath basin. Other bacterial isolates include E. coli (4.55%, S. aureus (4.55%), Enterobacter (2.77%), Streptococcus (2.27%), Coagulase Negative Staphylococcus (4.55%), Bacillus spp. (4.55%, other gram negative rods (4.55%, and other gram negative cocci (11.36%). Results implied that the presence of these identified bacteria have a higher possibility of disease transmission to the newborns, and that meticulous cleaning and disinfection of the bath basin is strongly recommended for prevention of diseases. The results obtained from this study provide awareness to the healthcare personnel at the NICU and suggest immediate action for disease prevention and health promotion among newborns.